2016
DOI: 10.1016/j.polymdegradstab.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on Poly(ε-caprolactone) film degradation at extreme pH values

Abstract: a b s t r a c tThe present paper studies the effect of pH on hydrolytic degradation of Poly(ε-caprolactone) (PCL) Degradation of the films was performed at 37 C in 2.5 M NaOH solution (pH 13) and 2.5 M HCl solution (pH 1). Weight loss, degree of swelling, molecular weight, and calorimetric and mechanical properties were obtained as a function of degradation time. Morphological changes in the samples were carefully studied through electron microscopy. At the start of the process the degradation rate of PCL film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 54 publications
12
61
0
2
Order By: Relevance
“…Results revealed adding PPy to the fibers can slow down the weight loss almost by 8% in this mixture and it can help to control the degradation rate of mats. The degradation of polysaccharides in a PBS solution mostly occurs due to the scission of macromolecular chains via a hydrolysis mechanism and it causes the slightly high weight loss in PCL/chitosan sample . Hydrophilic bonds of chitosan among the PCL chain could react with aqueous environment in PBS solution and speed up the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed adding PPy to the fibers can slow down the weight loss almost by 8% in this mixture and it can help to control the degradation rate of mats. The degradation of polysaccharides in a PBS solution mostly occurs due to the scission of macromolecular chains via a hydrolysis mechanism and it causes the slightly high weight loss in PCL/chitosan sample . Hydrophilic bonds of chitosan among the PCL chain could react with aqueous environment in PBS solution and speed up the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…However, the porosities of the scaffolds in this study did not differ significantly making it difficult to study its effect in this case and whether it would counteract the observed morphological stability for the highest crosslink density scaffolds. In addition to changes in crystallinity [ 13 , 14 , 15 , 31 ], crosslinking density [ 13 , 31 , 36 ] and macroscopic size and shape [ 13 , 30 , 38 , 39 ] discussed above, the degradation rate can be further tailored by e.g., copolymerization or blending [ 48 , 49 , 50 ], changing degradation media [ 51 ], end-group modification [ 52 ] or by adjusting molecular weight [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, degradation by-products should not elicit a toxic response and must be suitable for renal clearance (<30 kDa). 7 Additionally, the rate of degradation and the accompanied changes in material properties are critical. 8 For instance, in the case of scaffolds, degradation rate should closely match the rate of neotissue ingrowth to maximize healing.…”
mentioning
confidence: 99%